Osasco: JOC, ACO e PO no movimento operário (1960-1970) - Jesus, Paulo Sérgio de (2007)
This essay aims the analysis of the relation between: militants of Juventude Operária Católica - "JOC" (Catholic Workers Youth), Açao Catolica Operaria - "ACO" (Catholic Workers Action), Frente Nacional de Trabalho - "FNT" (National Labor Pool), Pastoral Operária - "PO" (Pastoral of Workers) and the worker class in the city of Osasco, in the 1960's and 70's. Based on the constituition of JOC, ACO and PO in Santo Antonio and Imaculada Conceiçao churches, I tried to bring out the proposals and tendencies according to the military regime and the present workers. So, I noticed the plurality of existing positions and the ambiance of disputes in which are constituted the catholic workers movements, where different interpretations of work relations and catholic doctrine, for example, were debated and improved. The sources analysis showed that it is possible to observe a transformation in the movements throughout this period. We can notice the search for alternatives of solution for workers issues, those movements radicalize their speech and point to a construction of new strategies of fight and worker resistance. Declining an accidental view of the History, the construction of a new syndicalism and base syndicalism did not happen by chance, since the strikes of 1978, neither essentially starting from the Steelworkers Union of SA Bernardo. In the history reconstruction of the work class in Osasco, it is necessary to consider, beside other forces, the acting of catholic militants in the worker and syndical movement and to realize its influence on the authentic syndicalism, mainly in ABC paulista region